40S hnRNP particles are a novel class of nuclear biomolecular condensates. Issue 11 (10th June 2022) - Domanski, Michal; Dedic, Emil; Pérez, Maria Escura; Cléry, Antoine; Campagne, Sébastien; Uldry, Anne-Christine; Braga, Sophie; Heller, Manfred; Rabl, Julius; Afanasyev, Pavel; Boehringer, Daniel; Nováček, Jiří; et al.
Abstract: Heterogenous nuclear ribonucleoproteins (hnRNPs) are abundant proteins implicated in various steps of RNA processing that assemble on nuclear RNA into larger complexes termed 40S hnRNP particles. Despite their initial discovery 55 years ago, our understanding of these intriguing macromolecular assemblies remains limited. Here, we report the biochemical purification of native 40S hnRNP particles and the determination of their complete protein composition by label-free quantitative mass spectrometry, identifying A-group and C-group hnRNPs as the major protein constituents. Isolated 40S hnRNP particles dissociate upon RNA digestion and can be reconstituted in vitro on defined RNAs in the presence of the individual protein components, demonstrating a scaffolding role for RNA in nucleating particle formation. Finally, we revealed their nanometer scale, condensate-like nature, promoted by intrinsically disordered regions of A-group hnRNPs. Collectively, we identify nuclear 40S hnRNP particles as novel dynamic biomolecular condensates.